A metastable phase Al3Cu2 - Ramachandrarao P.; Laridjani M. (My University, 2025)
A new metastable intermediate phase having a trigonal unit cell belonging to the space group P-3ml has been detected in a rapidly solidified aluminium-45 at. % copper alloy. The unit cell dimensions are a=4.106 and c=5.094 å. With five atoms per unit cell, the observed structure can be regarded as an isotype of Al3Ni2. © 1974 Chapman and Hall.